Intertextual interventions in the novels of Marlene Streeruwitz and Lilian Faschinger - Hallam, Lynne (2012)
This thesis considers prose texts by the Austrian authors Marlene Streeruwitz and Lilian Faschinger from the viewpoint of intertextuality. The research does not rely on the narrow definitions of intertextuality which are concerned with the appearance of an anterior text in a later text, or on studies of source and influence. Rather my treatment of the novels considers the way meanings are constructed by a network of cultural and social discourses which embody distinct codes, expectations and assumptions. This study discusses the ways in which the chosen texts, through their intertexts, display a postmodern impetus towards reappropriating authorized discourse in new and challenging ways, from feminist perspectives. My intertextual readings are alert to two main threads – the critique of aspects of Austrian society evident in the novels of Streeruwitz and Faschinger and their place within the tradition of Österreich-Beschimpfung, and the interventions into issues pertaining to gender. I examine thematic similarities and differences in the texts, which draw attention to specifically Austrian or gender related issues, as well as scrutinizing formal and linguistic elements. Ultimately, my thesis poses and suggests answers to questions regarding strategies of intervention by feminist authors and the fruitfulness of intertextual readings.